Nosocomial Infections: Pathogenicity, Resistance and Novel Antimicrobials - Wu, Lin; Wu, Zhi Cheng; Todosiichuk, Tetiana; Korneva, Oleksandra (Innovative Biosystems and Bioengineering, 2021)
Background. The fight against the spread of infectious diseases creates the problem of resistance to pathogens and the most resistant of them – the propagators of nosocomial infections – are formed in hospitals because of a number of reasons. The solution of the problem lies in different areas, but the search of new effective means for the treatment of such diseases remains relevant right today. The shortest way to do this is to find the "pain points" of the pathogens themselves, i.e. the factors of their pathogenicity and resistance to which the action of novel antiseptics should be directed. Objective. We aimed to analyse and evaluate the main factors of pathogenicity and resistance of pathogens of nosocomial infections to determine modern approaches to the development of novel antimicrobials. Methods. Search and systematization of new scientific data and results concerning pathogenic factors of microbial pathogens that can be used as targets for the action of drugs. Results. Over the last 10–20 years, due to the development of new research methods in biology, it has become possible to clarify the features and additional conditions for the detection of pathogenic factors of nosocomial infections. Additional mechanisms of manifestation of resistance, adhesiveness, invasiveness, transmission of signs, secretion of toxins by pathogens are shownthat determines the general increase of their resistance to the action of currently used means. The general idea of ​​creating antiseptics that will not increase the resistance of pathogens can now be implemented by using substances with multidirectional or indirect mechanisms of action that minimally affect the metabolism of the cell and significantly reduce its resistance and pathogenicity. Conclusions. Factors of pathogenicity of propagators of nosocomial infections and mechanisms of their implementation can be considered as the main targets for the action of novel antiseptics that will inhibit the spread of pathogens without increasing their resistance. The promising substances for such drugs, among other things, are bacteriophages and their modifications, enzybiotics, immunobiotics, autoinducer inhibitors, quorum sensing-system inhibitors, b-lactamase inhibitors and others. Some of these substances in combination with the new generation of antibiotics significantly enhance their effectiveness and together they are able to overcome the resistance of even multidrug-resistant pathogens.